Hubungan Status Gizi dan Kualitas Tidur dengan Kesehatan Mental Mahasiswa - Syarfaini; Nildawati; Alam, Syamsul; Rini, Rini Jusriani; Adha, Andi Syamsiah (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2024)
Adolescence is a unique and formative period. Physical, emotional and social changes, including poverty, abuse or violence, can make adolescents vulnerable to mental health problems, which will result in decreased nutritional status. This study aims to determine the relationship between nutritional status and sleep quality with the mental health of students in the Public Health Study Program, Faculty of Medicine and Health Sciences, Alauddin State Islamic University, Makassar. This type of research is quantitative research using a cross sectional design. The location of the research was carried out at the UIN Alauddin Makassar campus, in August – October 2023. The population in this study were all students of the Public Health Study Program, Faculty of Medicine and Health Sciences, Alauddin State Islamic University, Makassar. The research sample was final year students of the Public Health Study Program, totaling 102 respondents, using a purposive sampling method, with inclusion criteria namely final year undergraduate students, namely active students in semester 7 and above and willing to be research subjects by filling out research informed consent. The data analysis used is univariate analysis and bivariate analysis which are analyzed using the SPSS application with the chi-square test, if the p-value <0.05, then H0 is rejected, meaning there is a relationship between the variables, conversely if the p-value>0.05, then H0 is accepted, meaning there is no relationship between the variables. The results of the study show that there is no significant relationship between nutritional status and students' mental health with p-value = 0.380 (p>0.05) 3) there is a significant relationship between sleep quality and students' mental health with p-value = 0.019 (p<0.05 ).